2004
DOI: 10.1016/s1521-6918(04)00087-3
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative leakage and abscess formation after colorectal surgery

Abstract: Anastomotic leaks following colorectal surgery may be divided into those which are clinically significant and those which are not. Leakage occurs in 3.4-6% of all colorectal cases. It is most commonly associated with rectal anastomoses, being clinically significant in 2.9-15.3% of cases. Mortality following a leak may be 6.0-39.3%. There is no evidence that preoperative bowel preparation reduces the rate and consequences of leaks. There is no evidence for the use of drains when an anastomosis has been made out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(38 citation statements)
references
References 0 publications
3
32
0
3
Order By: Relevance
“…Mileski et al [15] reported that the formation of end colostomy at re-operation in leaks following low anterior resections conferred a survival benefit over anastomotic repair with proximal defunctioning. Moreover, other long-term sequelae of anastomotic leaks include stricture formation, recurrence of cancer and poor anorectal function [16]. From our series, 75% of patients with a stoma formed at re-operation were reversed within a year following formation.…”
Section: Discussionmentioning
confidence: 76%
“…Mileski et al [15] reported that the formation of end colostomy at re-operation in leaks following low anterior resections conferred a survival benefit over anastomotic repair with proximal defunctioning. Moreover, other long-term sequelae of anastomotic leaks include stricture formation, recurrence of cancer and poor anorectal function [16]. From our series, 75% of patients with a stoma formed at re-operation were reversed within a year following formation.…”
Section: Discussionmentioning
confidence: 76%
“…The single factor consistently shown to predict leakage is a low rectal anastomosis [3]. Much research has been carried out to determine additional risk factors for AL and those reported include radiotherapy, male sex [4,5], smoking [6], perioperative treatment with cyclooxygenase 2 (COX-2)-selective nonsteriodal anti-inflammatory drugs (NSAIDs) [7], blood transfusion, obesity, atherosclerosis [8] and inflammatory bowel disease [3]. Better understanding of the risk factors for AL will not only improve the management of high-risk patients but will also allow for preventive treatments, such as creating a protective stoma.…”
Section: Introductionmentioning
confidence: 99%
“…The use of diverting stomas has also been associated with stricture formation. Because feces in the lower rectum induce distention, the absence of feces may induce atrophy of the muscle cells with subsequent stenosis (3,6). Treatment for postoperative anastomotic stricture varies from conservative to surgical treatment.…”
Section: Discussionmentioning
confidence: 99%